Manajemen Pembelajaran Guru Kelas Di Sekolah Dasar Negeri 75 Kabupaten Kaur Provinsi Bengkulu (Studi Deskriptif Kualitatif) - Danim, Sudarwan; Hayadi, Firman; Somantri , Manap (Manajer Pendididikan, 2024)
This research aims to describe the learning management of class teachers in state elementary school 75 kaur district. The research uses qualitative descriptive methods. Research subjects were the principal and class teachers at state elementary school 75 kaur district. Research data was obtained from interviews, observation and documentation. Research data analysis includes data reduction, data presentation, verification and drawing conclusions. Based on the research results, it can be concluded that the class teachers at state elementary school 75 kaur district have implemented the principles of learning management well, but there is still room for improvement and further development.